Cardiovascular Effects of Cydonia oblonga Miller (Quince). (10th October 2022) - Amerizadeh, Atefeh; Vaseghi, Golnaz; Esmaeilian, Nazgol; Asgary, Sedigheh
Abstract : Cydonia oblonga Miller (quince) is a monotypic genus in the Rosaceae family which used to treat or prevent many medical conditions such as diabetes, cancer, infections, and ulcer. This review will summarize the current state of knowledge available on botany, phytochemistry, and pharmacology of this plant with a focus on its effect on some cardiovascular risk factors such as diabetes, blood pressure, lipid profile, and body weight. Databases of Google Scholar, Web of Science, PubMed, Scopus, and SID were searched systematically for English published articles with no date limitation. There were no human studies found, and all of the studies were conducted on animals or in vitro models. Reviewing of all 12 included articles showed that different types of quince extract have positive effects on cardiovascular-related factors such as blood pressure, diabetes, glucose metabolism, lipid profile, ROS, body weight, liver dysfunction, and thrombosis. An antihypertensive effect of quince showed to be a magnitude that is comparable to captopril and the lipid-lowering effect of quince showed to be a magnitude that is comparable to simvastatin. However, two studies evaluated the effect of quince fruit extract on insulin levels; one of them reported no positive effect, and the other one reported a significant positive effect. It can be concluded that different parts of quince including leaf, seed, and fruit could be used for improving cardiovascular-related factors including blood pressure, glucose metabolism and diabetes, obesity, and lipid-adjusting purposes. Quince was also found to have strong anti-inflammatory and antioxidant capacity. This study paves the way for further studies on the cardiovascular effect of quince consumption as a beneficial nutraceutical in humans.